Unpacking Righteousness: Material Legacies of Aid to Jews in Nazi-Occupied Poland - Lehrer, Erica (Holocaust and genocide studies, 2025)
In Poland, the figure of the "Righteous Gentile" who provided aid to Jews during the Holocaust has been highly politicized and instrumentalized by various actors across the political spectrum since the end of World War II, thus flattening a range of painfully complex intergroup and interpersonal interactions into superficial hagiographies. In Jewish communities abroad, the designation of "Righteous" is also more often sacralized than historicized. Poland is home to a vast landscape of so-called "post-Jewish" objects, such as clothing, bedding, and other household items, found in innumerable Catholic homes, taking the place of their (generally) murdered former owners. Emerging scholarship is beginning to address quotidian Jewish expropriation by Polish neighbors during and after the Holocaust. The present text links these two domains - discourses of Righteousness and the Polish Catholic "inheritance" of Jewish things in the context of Holocaust violence - which have thus far been studied separately, in pursuit of a material cultural approach to the experience of helping Jews. The author treats these objects as records of unequal encounters, which provide a unique opportunity to bring their former Jewish owners, as well as other relevant actors in stories of attempted survival, back into public view through reparative representations.